The TB12 method how to achieve a lifetime of sustained peak performance - Brady, Tom 1977- (Simon & Schuster, 2017)
Tom Brady explains how he developed his groundbreaking approach to long-term fitness, presenting a comprehensive, step-by-step guide to his personal practice. Brady offers the principles behind pliability, which is at the heart of a new paradigm shift and movement toward a more natural, healthier way of exercising, training, and living, and one that challenges some commonly held assumptions around health and wellness. Filled with lessons learned from Brady's own peak performance training, and step-by-step action steps to help readers develop and maintain their own peak performance, this book also advocates for more effective approaches to strength training, hydration, nutrition, supplementation, cognitive fitness, recovery, and other lifestyle choices that dramatically decrease the risk of injury while amplifying and extending performance, as well as quality of life.--